Enhancing hospital event-based surveillance system - Findings from a pilot study, Vietnam, 2017-2018 - Satoko Otsu; Hien Do; Tuan Anh Ha; Tu H. Ngo; Quang D. Tran; Orla Condell; Tuan V. Le; Nghia D. Ngu; Thanh V. Hoang; Tan Q. Dang; Phu D. Tran; Phuong T. N. Tran; et al. (Taylor & Francis Group, 2020)
In our inter-connected world, health-care professionals are the first line of defence to identify emerging diseases and public health events for rapid response. In Vietnam, event-based surveillance (EBS), critical for the early detection of emerging disease outbreaks and acute public health events, has been limited to media-based EBS until recently. In 2017-2018, the Ministry of Health of Vietnam, in collaboration with the World Health Organisation and the US Centres for Disease Control and Prevention, designed, implemented, and evaluated a hospital EBS demonstration pilot in six hospitals in two provinces in Vietnam. After the 9-month implementation period, we conducted a logbook review, eight interviews, and six focus group discussions with hospital and preventive medicine staff, and conducted thematic and descriptive analysis. During the implementation period, 11 signals were reported and confirmed as true events. Of the 11 signals, majority (N = 8, 72.7%) were detected in ICU, followed by the outpatient department (N = 2, 18.2%). The most common signal were clusters of food poisoning (N = 4, 36.4%). All (100%) signals were reported, risk-assessed, and responded to within 24 hours of signal detection. The hospital and preventive medicine staff reported that one of the main benefits of the pilot was their improved mutual relationship. This pilot formalised hospital event-based surveillance through a legal framework, standard operating procedures, a formal feedback mechanism to hospitals to facilitate a two-way conversation, and providing additional training and continued sensitisation. Most importantly, it fostered a trusting relationship between the curative medicine and public health sectors, marking an important step towards advancing the national event-based surveillance system in Vietnam.